The legal regulation of drugs and role of government: Perspectives from people who use drugs. (1st January 2020) - Greer, Alissa; Ritter, Alison
Highlights: The views of people who use drugs about legalized-regulated drug supply are diverse. People who use drugs support legalisation but have concern over the role of government. Findings underscore the need for user involvement and equity in future drug law reform. Abstract: Background: The legalization and regulation of currently illicit drugs has come to the forefront of drug policy debates in recent years, particularly in the context of cannabis legalization and the opioid crisis in North America. However, sufficient granularity on the various aspects of a legally regulated drug supply is missing from these debates. Further, the voices and opinions of people who use drugs have generally been absent from drug law reform deliberations. This study aimed to examine the views of people who use drugs and who are deeply impacted by drug policies to understand the perceived impacts and role of government under a legalized-regulated market. Methods: Four focus groups were held with people who use drugs in Sydney, Australia. Results: Most participants supported various models of legalization, although the perspectives on these models were diverse. Overriding these views was skepticism over the government's role in regulating a legal market, as well as concern for the personal agency of people who use drugs under a medically regulated drug supply model. Some participants discussed potential harms (e.g. increases in use and initiation), but emphasized the benefits (e.g. increases in quality and safety) from legal reform. Discussion: While there was support for legal models of drug supply regulation, findings have major implications in terms of how governments and medical systems may perpetuate the oppression of people who use drugs through regulation, and urge future drug policy deliberations to include broader perspectives from the affected community.